Perception of health inequalities in different social classes, by health professionals and health policy makers in Germany and the United Kingdom - Andreas Mielck (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 1998)
The paper focuses on the following question: What is known about the existence and the extent of health inequalities, their explanations and potential ways to reduce them, by members of the lower social class, by health professionals and by health policy makers? By health inequalities we mainly refer to differences in morbidity and mortality between socio-economic groups, i.e. differences in morbidity and mortality by education, occupation and income. The paper looks at the problem of health inequalities from an 'actor-perspective'. Concerning the perspective of health professionals and health policy makers, information is mainly provided from Germany, where the funding institution and the first author are based. Concerning the perspective of the lower social class, however, information is mainly provided from the United Kingdom. The United Kingdom is the Western European country with the greatest breadth of research on health inequalities; thus it can serve as a role model for Germany, where this kind of research is still rather limited. The review shows that we know very little about the perception of health inequalities by these actors. Research on health inequalities still seems to be rather isolated from the beliefs and values of the people most concerned, at least in Germany and in the United Kingdom. Promoting the discussion on the perception of health inequalities would help to develop strategies addressed at reducing them. – – In der Studie wird die Wahrnehmung der 'gesundheitlichen Ungleichheit' untersucht, d.h. die Wahrnehmung der in vielen empirischen Studien belegten Tatsache, daß Personen mit einem geringeren sozio-ökonomischen Status zumeist kränker sind und früher sterben als Personen mit einem höheren Status. Die folgende Frage steht im Mittelpunkt: Was wissen Angehörige der unteren sozialen Schichten, Akteure der gesundheitlichen Versorgung und der Gesundheitspolitik über die Existenz der gesundheitlichen Ungleichheit, die Erklärung und die mögliche Verringerung dieses Problems? Die Studie betrachtet das Problem der gesundheitlichen Ungleichheit somit von einer 'Akteur-Perspektive' aus. Bezogen auf Akteure der gesundheitlichen Versorgung und der Gesundheitspolitik werden vor allem Informationen aus der Bundesrepublik vorgestellt. Bezogen auf die Perspektive der unteren sozialen Schichten werden dagegen vor allem Studienergebnisse aus Großbritannien präsentiert. Der Überblick über den Stand der Literatur zeigt, daß sehr wenig über die Wahrnehmung der gesundheitlichen Ungleichheit bekannt ist. Die Forschungsfragen dieser Studie spielen offenbar weder für Wissenschaftler noch für Akteure der gesundheitlichen Versorgung und der Gesundheitspolitik eine bedeutende Rolle. Durch eine verstärkte Thematisierung dieser Fragen könnte ein Beitrag dazu geleistet werden, die Diskussion über Strategien der Verringerung gesundheitlicher Ungleichheit zu beleben.
Keywords: 300; Gesundheitspolitik; Öffentliche Meinung; Wahrnehmung; Gesundheit; Sterblichkeit; Sozialstruktur